Ab-initio study of L-Tartaric Acid (LTA) single crystal for NLO application. (November 2015) - Hasmuddin, Mohd.; Abdullah, M.M.; Singh, Preeti; Shkir, Mohd.; Vijayan, N.; Wahab, M.A
Abstract: Single crystals of LTA were grown by slow evaporation solution technique (SEST). Powder X-ray diffractometry (PXRD) confirmed the monoclinic crystal structure, whereas the high resolution X-ray diffractometry (HRXRD) ascertained the good crystalline perfection (FWHM=25 arcsec) of the as-grown single crystal. Optical study demonstrated the high optical transparency (85%). Photoluminescence (PL) spectroscopy illustrated the PL-emission at λ =388 nm and optical band gap ~3.2 eV. The SHG efficiency of LTA single crystal (6.61) is comparatively greater than the referenced (KDP) single crystal (6.08). Thermal analysis revealed that the crystal is thermally stable up to ~170 °C. The calculated value of the activation energy (Δ E ) and corrected hardness ( H 0 ) for the crystal were found to be equal to 1.16 eV and 46.66 kg/mm 2, respectively. The as-grown LTA single crystals can be used as a potential candidate for NLO material as well as in electronic and optoelectronic devices. Highlights: A single crystal of good crystalline perfection (FWHM=25 arcsec). Comparatively higher SHG efficiency (6.61) confirms good NLO properties. Electrically, thermally and mechanically efficient for NLO devices.